Wastewater influent and effluent concentrations from on-site package plants in Northern Sweden and Finland - Vidal, Brenda (Luleå University of Technology, 2023)
The data contains influent and effluent concentrations of traditional parameters measured in on-site package plants for domestic wastewater treatment serving single houses or small communities (2-30 person equivalent). The parameters analysed include organic matter, suspended solids, nutrients (phosphorus and nitrogen compounds) and indicator bacteria, as well as other physicochemical parameters such as temperature, pH and turbidity, and chloride as a tracer compound to detect dilution effects. Additional influent and effluent concentrations of micropollutants from two slightly larger plants (serving 12-30 person equivalent) are also included. These micropollutants consisted of 19 selected pharmaceuticals, caffeine and the sweetener Acesulfame K, and 15 phthalates.
The purpose of the collected dataset was to investigate the treatment efficiency of package plants operating in cold climate conditions throughout different seasons. The samples were collected in the northern regions of Sweden (Norrbotten) and Finland (North Ostrobothnia and Lapland) characterised by low winter temperatures and deep frost penetration.
The data has not been processed and consists of results (raw data) obtained directly from our university laboratory in Luleå university of technology (nutrient samples) and accredited laboratories (traditional parameters, microbiology, micropollutants).

The data contains influent and effluent concentrations of traditional parameters measured in on-site package plants for domestic wastewater treatment serving single houses or small communities (2-30 person equivalent). The purpose of the collected dataset was to investigate the treatment efficiency of package plants operating in cold climate conditions throughout different seasons. The samples were collected in the northern regions of Sweden (Norrbotten) and Finland (North Ostrobothnia and Lapland) characterised by low winter temperatures and deep frost penetration.
The investigated facilities included six package plants operated in continuous mode: one with a trickling filter (TF), one with a rotating biological contactor (RBC) and four with activated sludge with phosphorus removal by coagulation (ASC) or alkaline filter (ASF1, ASF2, ASF3) systems. Additionally, five plants supplied by three different manufacturers operated in batch mode with activated sludge and coagulation for phosphorus removal (SBR1-5).
The parameters analysed include organic matter (BOD), suspended solids (TSS), nutrients (phosphorus and nitrogen compounds) and indicator bacteria, as well as other physicochemical parameters such as temperature, pH and turbidity, and chloride as a tracer compound to detect dilution effects. Additional influent and effluent concentrations of micropollutants from two slightly larger plants (ASC and TF, serving 12-30 person equivalent) are also included. These micropollutants consisted of 19 selected pharmaceuticals, caffeine and the sweetener Acesulfame K, and 15 phthalates.

The data set contains multiple files:
-A main excel file called "Wastewater_package_plants" containing the numerical results of influent and effluent concentrations of traditional parameters and selected micropollutants.
- Three excel files called "Wastewater temp data..." containing temperature data logged continuously with a temperature sensor (placed in the biological treatment unit) at three different package plants
- Two text files called "SMHI Air temp data..." with air temperature data retrieved from the Swedish meteorological institute (SMHI) to be used with the wastewater temperature data

All the excel files are provided in xlsx and csv format.

Uppgifterna inkluderar inkommande och utgående avloppsvattenkoncentrationer av traditionella parametrar uppmätt i minireningsverk som betjänar enstaka hus eller små samhällen (2-30 personekvivalenter). Parametrarna som analyseras inkluderar organiskt material, suspenderade ämnen, näringsämnen (fosfor- och kväveföreningar) och indikatorbakterier, samt andra fysikalisk-kemiska parametrar som temperatur, pH och turbiditet samt klorid för att upptäcka utspädningseffekter. Ytterligare inflödes- och avloppskoncentrationer av mikroföroreningar från två lite större anläggningar (betjänar 12-30 personekvivalenter) ingår också. Dessa mikroföroreningar bestod av 19 utvalda läkemedel, koffein och sötningsmedlet Acesulfame K, och 15 ftalater.
Syftet med den insamlade datamängden var att undersöka reningseffektiviteten hos minireningsverk som arbetar under kalla klimatförhållanden under olika årstider. Proverna samlades in i de norra delarna av Sverige (Norrbotten) och Finland (Norra Österbotten och Lappland) som kännetecknas av låga vintertemperaturer och djup frostinträngning.
Uppgifterna har inte behandlats och består av resultat (rådata) som erhållits direkt från vårt universitetslaboratorium i Luleå tekniska universitet (näringsprover) och ackrediterade laboratorier (traditionella parametrar, mikrobiologi, mikroföroreningar).

Uppgifterna innehåller inkommande och utgående avloppskoncentrationer av traditionella parametrar uppmätta i minireningsverk för rening av hushållsavloppsvatten som betjänar enstaka hus eller små samhällen (2-30 personekvivalenter). Syftet med insamlingen av data var att undersöka reningseffektivitetet av minireningsverk som arbetar under kalla klimatförhållanden under olika årstider. Proverna samlades in i de norra delarna av Sverige (Norrbotten) och Finland (Norra Österbotten och Lappland) som kännetecknas av låga vintertemperaturer och djup frostinträngning.
De undersökta anläggningarna inkluderade sex minireningsverk som drivs i kontinuerligt läge: en med biofilter (trickling filter) (TF), en med biorotor (RBC) och fyra med aktivt slam med fosforfällning genom koagulering (ASC) eller alkaliskt filter (ASF1, ASF2 , ASF3) system. Dessutom kördes fem anläggningar från tre olika tillverkare i batchläge med aktivt slam och koagulering för fosforfällning (SBR1-5).
Analyserade parametrar inkluderar organiskt material (BOD), suspenderade partiklar (TSS), näringsämnen (fosfor- och kväveföreningar) och indikatorbakterier, såväl som andra fysikalisk-kemiska parametrar som temperatur, pH och grumlighet, och klorid som spårämne för att detektera utspädningseffekter. Ytterligare inflödes- och avloppskoncentrationer av mikroföroreningar från två större anläggningar (ASC och TF, som betjänar 12-30 personekvivalenter) ingår också. Dessa mikroföroreningar bestod av 19 utvalda läkemedel, koffein och sötningsmedlet Acesulfam K, och 15 ftalater.

Datasetet innehåller flera filer:
-En huvudsaklig excel-fil som heter "Wastewater_package_plants" som innehåller de numeriska resultaten av inkommande och utgående koncentrationer av traditionella parametrar och utvalda mikroföroreningar.
- Tre excelfiler kallade "Wastewater temp data..." innehållande temperaturdata som loggas kontinuerligt med en temperatursensor (placerad i den biologiska reningsenheten) vid tre olika förpackningsanläggningar
- Två textfiler kallade "SMHI Air temp data..." med lufttemperaturdata hämtade från Sveriges meteorologiska institut (SMHI) för att användas med avloppsvattnets temperaturdata

Alla Excel-filer tillhandahålls i xlsx- och csv-format.
Avloppsvattens inkommande och utgående koncentrationer från minireningsverk i norra Sverige och Finland
Keywords: on-site waste water treatment; behandling av avloppsvatten på stället; micropollutant; mikroförorening; nitrogen; kväve; pharmaceutical waste; farmaceutiskt avfall; phosphorus; fosfor; bacteria; phthalates; bacteria; bakterier; package plant; minireningsverk; on-site wastewater treatment; enskilda avlopp; phthalates; ftalater; treatment efficiency; reningseffektivitet; Water Engineering; Vattenteknik; Environmental Management; Miljöteknik och miljöledning